The Effect of Kepok Banana Starch Substitution (Musa paradisiaca L.) Modifications on the Texture and Color of Mocaf Flour Caramel Sponge - Nadia Aqiela Laili; Aan Sofyan (Engineering Proceedings, 2024)
This research aimed to determine the effect of modified kepok banana starch substitution on the texture (hardness, adhesiveness, cohesiveness, and gumminess) and caramel sponge color with four different modified starch substitution percentages. This research is experimental research with RAL (Completely Randomized Design). The research results show that the values of hardness for caramel sponge cake were 27.48 N, 26.89 N, 26.86 N, and 16.66 N. The values of adhesiveness were 0.38 Nmm, 0.14 Nmm, 0.63 Nmm, and 1.21 Nmm. The cohesiveness values for the caramel cake were 0.34, 0.43, 0.40, 0.31. The values of gumminess were 9.85 N, 11.90 N, 11.02 N, 5.20 N. The L values for caramel cake were 26.61, 25.92, 32.00, and 32.31. The a values for caramel cake were 7.22, 8.83, 8.34, and 6.73, whereas the b values were 15.17, 13.64, 14.84, and 11.56. This research demonstrates that there is an effect of modified kepok banana starch substitution on the texture profile of hardness and on the L value of caramel cake color.